From an Object to a Tool: On Possible Transformations of Analysis of the Border Problem - Zaporowski, Andrzej (Journal of cognition and culture, 2025)
The article addresses the border as an object and yet a tool found in the cultural realm, where the object is approached in three stages. Firstly, the border problem is given the form of an assembled representation, and which becomes an object of one’s reflection. Secondly, this object turns into an obstacle as one faces both the abstract and the concrete references of the representation in question. Thirdly, this obstacle requires some steps to cope with it by one; one becomes a user of the assembled representation, where the object becomes a tool. The divisions suggested by the representation are conditioned by means of the cultural actions. Culture as a set of particular attitudes like belief, intention and assessment allows of approaching the border as both an object and a tool, where not only manipulation but also responsibility and creativity is crucial.